STUDI PERANCANGAN KOREOGRAFI ANAK MELALUI REVITALISASI SENI TRADISIONAL REOG KALOKA - Trie Wahyuni dan Ni Nyoman Seriati (Jurnal Kependidikan, 2009)
The study was aimed at improving the aesthetic experience of Reog art community KALOKA, improving the appreciation of folk art and the childrens choreography design through folk traditional art revitalitation on reog KALOKA. Conducted in Suru Kemadang Tanjungsari Gunungkidul Yogyakarta, from May to December using action research design, the subjects of the research included actors, group leader, coach and players. The action research was conducted in two cycles, Cycle I in 6 meetings Cycle II in 8 sessions. The researcher served as the action performer, the group leader as the collaborator, and two students as coaches. The results showed that: the design should be in line with the movement characteristics of children of elementary and junior high schools which consisted of eleven main movements: a) napak satu menthangan nekuk walk; b) forward mipil walk, shoulder movement 2; c) making formation, jengkeng, pacak gulu coklekan; d) sembahan, heads coklekan, right and left; e) standing, mipil walk leg gedrug-gedrug; f) awe-awe movement; g) moving forward uniformly ngracik, making the perpendicular floor pattern with shoulder movement; h) walk in place, kuda jengkeng formation place in the stand position 9 side by side), carrying; i) walk in place, sitting in circle while clapping hands, movement in place face to face dolanan asto, movement in place lonthangan; j) taking the horse together, gedrug-gedrug movement; and k) mipil walk (both hand holding the horse) 4 line formation, moving forward together with shoulder movement variation, moving backward together with shoulder movement variation. Mipil walk, make a large circle, in line.